DYNAMIC EFFECTS OF CHANGE IN GOVERNMENT EXPENDITURE IN THE NEPALESE ECONOMY - Adhikari, Gyan Mani; Gnawali, Achyut; Joshi, Binod; Chhetri, Santosh; Karki, Krishna Bahadur (JURNAL STIE SEMARANG, 2025)
One of the central tenets of macroeconomics is that fiscal policy can effectively stabilize the economy and achieve macroeconomic targets. In the last few decades, monetary policy tools have been widely used to achieve this goal. There has been, however, a renewed interest in using fiscal policy as a stabilizing tool since the onset of the recent Global Financial Crisis. This study analyses the effects of changes in government expenditure on aggregate economic activity and how these effects are transmitted in the case of Nepal for the period 1990–2023. To analyze the transmission mechanism of government spending innovations, the Vector Autoregressive Model (VAR) is estimated for the following five variables: government expenditure, real GDP, private consumption, debt-to-GDP ratio, interest rate, and real exchange rate. The consumption and output respond negatively to the innovation in government expenditure, consistent with the standard neoclassical model. The interest rates increase in the face of expansionary fiscal spending. As government debt, builds up with fiscal expansion, the rising risk of default or increasing inflation risk reinforces crowding out through interest rates. The real exchange rate tends to appreciate in response to a rise in government spending. This finding is based on open economy literature and conventional literature.